2009
DOI: 10.2147/vhrm.s4711
|View full text |Cite
|
Sign up to set email alerts
|

RhoA/Rho-kinase signaling: a therapeutic target in pulmonary hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a devastating disease characterized by progressive elevation of pulmonary arterial pressure and vascular resistance due to pulmonary vasoconstriction and vessel remodeling as well as inflammation. Rho-kinases (ROCKs) are one of the best-described effectors of the small G-protein RhoA, and ROCKs are involved in a variety of cellular functions including muscle cell contraction, proliferation and vascular inflammation through inhibition of myosin light chain phosphatase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 105 publications
1
39
0
1
Order By: Relevance
“…In addition to the STAT3-NFAT axis, the antiproliferative and proapoptotic effect of SHP2 inhibition by siRNA or miR-204 mimic could also be attributed to the inhibition of the RhoA-ROCK (Rho-associated, coiled-coilcontaining protein kinase) pathway (Fig. S6 D; Lee and Chang, 2008;Kimura and Eguchi, 2009), which is increased and implicated in PAH-PASMC proliferation (Barman et al, 2009). Based on the fact that miR-204 is encoded within TRPM3 (Wang et al, 2010) (Fig.…”
Section: Src Activation By Mir-204 Promotes Stat3 and Nfat Activationmentioning
confidence: 99%
“…In addition to the STAT3-NFAT axis, the antiproliferative and proapoptotic effect of SHP2 inhibition by siRNA or miR-204 mimic could also be attributed to the inhibition of the RhoA-ROCK (Rho-associated, coiled-coilcontaining protein kinase) pathway (Fig. S6 D; Lee and Chang, 2008;Kimura and Eguchi, 2009), which is increased and implicated in PAH-PASMC proliferation (Barman et al, 2009). Based on the fact that miR-204 is encoded within TRPM3 (Wang et al, 2010) (Fig.…”
Section: Src Activation By Mir-204 Promotes Stat3 and Nfat Activationmentioning
confidence: 99%
“…29 RhoA and Rho kinase have long been associated with the development of PAH and this pathway has been proposed as a potential target for PAH therapy. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Blood vessel contraction induced by agonist is mainly due to an increase in intracellular Ca 2+ concentration by increased membrane depolarization or phospholipase C (PLC)-mediated Ca 2+ release from the sarcoplasmic reticulum (24,25). It has been reported that the RhoA/Rho kinase pathway acts as a Ca 2+ sensitizer during smooth muscle contraction and that abnormal Ca 2+ sensitization provokes the pathophysiology of hypertension, arterial restenosis, and pulmonary hypertension (26)(27)(28). A thromboxane-A2 mimic compound, U46619, activates the RhoA/Rho kinase pathway, which phosphorylates and activates the myosin phosphatase inhibitor CPI17 in VSMCs, resulting in inhibition of myosin light chain phosphatase (MLCP), which induces vasodilation (23).…”
Section: Discussionmentioning
confidence: 99%